Reproducibility of left and right ventricular mass measurements with cardiac CT - Schwarz, Florian; Takx, Richard; Schoepf, U. Joseph; Lee, Yeong Shyan; Ruzsics, Balazs; Gassner, Eva Maria; Chiaramida, Salvatore; Henzler, Thomas (Journal of cardiovascular computed tomography, 2011)
Background - Cardiac CT provides volumetric data that enables characterization of the myocardium. Objective - We evaluated intraobserver, interobserver, and interstudy reproducibility of left ventricular (LV) and right ventricular (RV) mass quantification with cardiac CT. - Methods - Thirty-eight patients who underwent cardiac CT twice within 365 days were included in this analysis. Functional reconstructions in 10% steps throughout the R-R interval and axial 1.5-mm sections were used. Semiautomatic contour detection was used to trace epicardial and endocardial borders in all cardiac phases for calculation of LV and RV ejection fraction, end-diastolic volume, end-systolic volume, cardiac output, stroke volume, and ventricular mass. For each study 2 observers measured LV and RV mass twice. - Results - LV mass parameters derived from semiautomatic contour detection algorithm had excellent intraobserver (r = 1.00), interobserver (r = 0.99), and interstudy (r = 0.99) reproducibility (P < 0.0001). Average end-diastolic LV mass was 146.2 ± 42.9 g at the first CT study and 146.8 ± 44.4 g at the second study. For measuring RV mass, reproducibility was good on all levels (r = 0.78, r = 0.78, and r = 0.68, respectively, with an average end-diastolic mass of 25.7 ± 5.8 g at the first study and 24.4 ± 4.8 g at the second study. - Conclusion - Quantification of LV mass at cardiac CT with the threshold-based, region-growing semiautomatic segmentation analysis software evaluated here is highly observer independent and reproducible. This largely holds true for the estimation of RV mass as well; however, further improvements are needed to optimize reproducibility for RV mass quantification.
Gesehen am 28.10.2022